Rethinking "means-as-end": Methodological potentials of socially engaged research - Miloš Milenković (University of Belgrade, 2016)
We explore Bennet’s suggestion that an entire sub-disciplinary tradition within applied anthropology, namely the action anthropology, was built on specific methodolo gical algorythm, "means-as ends", derived from pragmatic logic of discovery and adapted to ethnographic research. Following the founder of the interdisciplinary reflective methodology John Dewey and his unifying logic of scientific discovery, social criticism and pedagogic-activist oriented research, Sol Tax intended to establish the tradition of action anthropology, which saw both its peak and ending in the illustrious The Fox Project. Our aim, apart from the critical recapitulation of the methodology used in the Fox Project, logical-methodological analysis of Dewey’s logic of discovery applied to anthropology, and the reinterpretation of the general point of this episode from disciplinary history, is to analyze the implications of this research option for future anthropologic research.